The #dirumahaja as a People Movement on Twitter - Zuly Qodir; Vindhi Putri Pratiwi; Mega Hidayati; Hasse Jubba (FISIP Universitas Atma Jaya Yogyakarta, 2022)
The central and local governments must continue synergizing to reduce the spread of Covid-19. Policies that the Indonesian government implemented are social distancing and self-quarantine. The #dirumahaja movement emerged on various social media platforms, including Twitter. This paper analyzes the use of Twiter as a platform for #dirumahaja movement, to understands people’s attitude in dealing with Covid-19. The findings show that becomes a public space. Through hashtags on Twitter, the public communicate and support government policies related to social distancing and self-quarantine.